2007
DOI: 10.1038/sj.mp.4002062
|View full text |Cite
|
Sign up to set email alerts
|

The pipeline and future of drug development in schizophrenia

Abstract: While the current antipsychotic medications have profoundly impacted the treatment of schizophrenia over the past 50 years, the newer atypical antipsychotics have not fulfilled initial expectations, and enormous challenges remain in long-term treatment of this debilitating disease. In particular, improved treatment of the negative symptoms and cognitive dysfunction in schizophrenia which greatly impact overall morbidity is needed. In this review we will briefly discuss the current pipeline of drugs for schizop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
112
0
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 168 publications
(114 citation statements)
references
References 162 publications
(193 reference statements)
0
112
0
2
Order By: Relevance
“…21 Therefore, 5-HT 2C presents an intriguing but challenging target for therapeutics (i.e., agonism at 5-HT 2C in the mesolimbic dopamine pathway may reduce dopaminergic transmission and improve positive symptoms of schizophrenia). However, a concern is that dopaminergic suppression via 5-HT 2C agonism in the mesocortical pathway could potentially worsen cognition, 22 whereas, in the nigrostriatal pathway the same action might cause EPS. [23][24][25] On the other hand, 5-HT 2C antagonism at inhibitory gamma-aminobutyric acid (GABA) interneurons in the brain stem may be expected to reduce depression and improve cognition by disinhibiting dopamine and norepinephrine release in the prefrontal cortex.…”
Section: -Ht 2c : Agonist or Antagonist?mentioning
confidence: 99%
See 1 more Smart Citation
“…21 Therefore, 5-HT 2C presents an intriguing but challenging target for therapeutics (i.e., agonism at 5-HT 2C in the mesolimbic dopamine pathway may reduce dopaminergic transmission and improve positive symptoms of schizophrenia). However, a concern is that dopaminergic suppression via 5-HT 2C agonism in the mesocortical pathway could potentially worsen cognition, 22 whereas, in the nigrostriatal pathway the same action might cause EPS. [23][24][25] On the other hand, 5-HT 2C antagonism at inhibitory gamma-aminobutyric acid (GABA) interneurons in the brain stem may be expected to reduce depression and improve cognition by disinhibiting dopamine and norepinephrine release in the prefrontal cortex.…”
Section: -Ht 2c : Agonist or Antagonist?mentioning
confidence: 99%
“…54,55 As a result of these findings, N-desmethylclozapine (ACP-104) and other M 1 receptor agonists are in clinical trials as potential treatments of the cognitive dysfunction of schizophrenia. 22 …”
Section: Learning From Side Effectsmentioning
confidence: 99%
“…This hypothesis has led to a new crop of muscarinic subtype-selective allosteric potentiators currently being developed (Conn and Roth, 2008;Gray and Roth, 2007). Furthermore, it has also been shown that clozapine can potentiate NMDA activity by directly binding to glycine B site (Bressan et al, 2005;Javitt et al, 2005;Schwieler et al, 2008), thus contributing to its unique clinical efficacy.…”
Section: Implications Of These Findings For Psychiatric Drug Discoverymentioning
confidence: 99%
“…Importantly, atypical antipsychotic drugs like clozapine are unique in their ability to normalize PCP-induced disruption of PPI (Bakshi Figure 1 Mining the druggable genome identifies molecular targets for clozapine action. (a) Results from hierarchical clustering analysis of affinities of approved typical and atypical antipsychotic drugs at molecular targets implicated in antipsychotic drug action (Gray and Roth, 2007;Roth et al, 2004). See Supplementary Table 2 for complete data set.…”
Section: The Presynaptic Component Of Serotonin Neurons Is Essential mentioning
confidence: 99%
See 1 more Smart Citation